Dissemination on Rice’s New High Yielding Variety Through Demonstration Farming of Jajar Legowo Technology in East Java - Tri Sudaryono (Graduate Program, 2017)
Agricultural Research Agency has innovated Integrated Crop Management (ICM) of lowland rice. This innovation has been adopted and developed by the General of Food Crop Directorate and implemented in the form of Field School. The constituent technology components of ICM continues to be refined over time. Various components of the resulted technology are assembled into a technology package called Jajar Legowo Super of Rice Technology. The intactly application of this technology by farmers accompanied by intensive facilitation is believed to be able to produce yield at least 10 tons of Drain Grain Harvest (DGH)/ha in each season, compared to the yield of rice cultivated by farmers which is only about 6 tons of DGH/ha. Accelerating the dissemination of Rice’s New Superior Varieties through Demonstration Farming (Demo farm) of Jajar Legowo Super Technology in East Java was conducted in Central Sadar Village, Mojoanyar Subdistrict, Mojokerto Regency involving Mardi Tani Farmer Group. The activity was held at Dry Season II (June - November 2016). Through this activity, it is expected to accelerate the spread and the increasing implementation of rice farming technology adoption through the approach of Jajar Legowo Super which has an impact on the increasing efficiency of farming. Results show that the use of Certified Superior Seed Varieties (CSSV) through demo farm of Jajar Legowo Super increases productivity between 12.26-32.03%, improves farmers' efficiency and income, and generates about 25 tons of Extention Seed (ES) and Stock Seed (S) paddy seeds. In addition, from this activity it is confirmed that adopting the technology components of Jajar Legowo Super by farmers increases significantly if compared to both before and after demo farm. The highest adoption increase about 60% is shown in components using Rice Field Test Kit (RFTK) and biological fertilizers.Keywords: Dissemination, Jajar Legowo Super, Rice, Technology